Chapter 10 One Medicine? Advocating (Inter)disciplinarity at the Interfaces of Animal Health, Human Health, and the Environment - Cassidy, Angela (Rutgers University Press, 2016)
This chapter discusses the recent emergence of advocacy for 'One Health' (OH): the idea that greater interdisciplinarity across the domains of human and animal health research, clinical practice and policy is essential for addressing contemporary problems such as zoonotic disease, food safety, cancer and drug development. Over the past decade, the language of OH has been taken up by increasingly prominent actors in global health and biomedicine, including funders, international agencies and pharmaceutical companies; however, there has been a long history of veterinary led advocacy for similar ideas since the late 19th century. This longer history raises an immediate question: given that ideas of collaboration and convergence between human and veterinary medicine have been being advanced for such a long time, why has OH come to the fore at this particular point in time? This chapter analyses the emergence and growth of OH, following the key actors, events, disciplines, and agendas that have contributed to its increasing popularity, while tracing its origins in the histories of animal health, global development, and infectious disease. Using bibliometrics of key OH terms in academic journals, alongside qualitative analysis of academic, policy, and online documents, this chapter shows that while OH has been adopted by institutions across human and animal health, it is predominantly used by scientists publishing in veterinary science journals. This raises questions about the extent to which OH is interdisciplinary, to which actors and in which contexts: to what extent is it a 'top-down' or 'bottom-up; version of interdisciplinarity? The implications of these findings in the broader context of agenda-building across the life and environmental sciences of the early 21st century are then discussed.